2017
DOI: 10.18632/oncotarget.17261
|View full text |Cite
|
Sign up to set email alerts
|

Identification of deubiquitinase targets of isothiocyanates using SILAC-assisted quantitative mass spectrometry

Abstract: Cruciferous vegetables such as broccoli and kale have well documented chemopreventative and anticancer effects that are attributed to the presence of isothiocyanates (ITCs). ITCs modulate the levels of many oncogenic proteins, but the molecular mechanisms of ITC action are not understood. We previously reported that phenethyl isothiocyanate (PEITC) inhibits two deubiquitinases (DUBs), USP9x and UCH37. DUBs regulate many cellular processes and DUB dysregulation is linked to the pathogenesis of human diseases in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 118 publications
(131 reference statements)
2
14
0
Order By: Relevance
“…The docking data was further confirmed by Ub‐VS assay in which BITC only at 50 μM could inhibit the USP14′s activity (Figure ). Our data may have provided an explanation for why USP14 was not found to be a target of ITCs in previous studies under their experimental conditions …”
Section: Discussionmentioning
confidence: 55%
“…The docking data was further confirmed by Ub‐VS assay in which BITC only at 50 μM could inhibit the USP14′s activity (Figure ). Our data may have provided an explanation for why USP14 was not found to be a target of ITCs in previous studies under their experimental conditions …”
Section: Discussionmentioning
confidence: 55%
“…Once a protein is conjugated with a poly-ubiquitin chain, it is recognized and degraded by the proteasome system [56]. PEITC has been reported to induce ubiquitination through the inhibition of deubiquitinase activity [57]. MicroRNAs may also play a role in the regulation of MTDH expression by PEITC.…”
Section: Discussionmentioning
confidence: 99%
“…PEITC also decreases the levels of DUBs by initiating their degradation 68. Another mechanism by which PEITC could regulate the epigenome is by altering the expression of a number of microRNAs (miRNAs) 69.…”
Section: Peitc and Epigenetic Regulation: An Emerging Fieldmentioning
confidence: 99%
“…Recently, Lawson and colleagues found that, possibly through the modification of their cysteines, PEITC targets various deubiquitinases (DUBs) many of which (e.g., VCPIP1, USP1, USP3, USP16, and USP48) are involved in chromatin remodeling and DNA repair. PEITC also decreases the levels of DUBs by initiating their degradation . Another mechanism by which PEITC could regulate the epigenome is by altering the expression of a number of microRNAs (miRNAs) .…”
Section: Peitc and Epigenetic Regulation: An Emerging Fieldmentioning
confidence: 99%